Do bacharelado a docência: percepções dos egressos do PEG/UFSM quanto a atuação profissional docente - Santos, Cristiane Berenice Caraveta dos (2017)
This research is part of the Public Policy and Management line, linked to the Master's Course in Professional and Technological Education of the Industrial Technical College of Santa Maria and of the Federal University of Santa Maria ITCSM/FUSM and consisted in analyzing the perceptions of the graduates of the Special Program of Graduation (SPG) for Teacher Training for the Professional Education of the FUSM, in relation to their formation and action as teachers. Thus, it was sought to identify the perceptions of the graduates of the period between 2010-2015, who act or acted in teaching, with a view to outlining their professional profile and analyzing these perceptions. Based on the perspective of authors such as: Tardif, Nòvoa, Garcia, Zabalza, Cunha, Gauthier, the research is characterized as case study. A semi structured questionnaire was used online through the Google Forms platform, and interviews through the Whatsapp application. Nine hundred and fifty-two questionnaires were sent and four interviews were conducted. The information was selected according to the inclusion and exclusion criteria established for the research and submitted to content analysis. Finally, the results showed that the graduates understand the dimensions involved in the in the teacher's activities and the need for innovation and dynamism in the classes, however, it is noticed, through the reports, that their classes are guided by the reproduction of traditional procedures.